Effect of Aqueous and Ethanol Extract of Acacia nilotica L. Leaves on Seed Germination of Vigna radiata L. - Nailul Rahmi Aulya (Fakultas Keguruan dan Ilmu Pendidikan, 2020)
This research aimed to tested the effect of extract on Vigna radiata L. germination. Tested the effect of crude extract of A. nilotica leaves on germination was conducted experimentally using Factorial Completely Randomized Design (FCRD). The first fact or was the type of crude extract and the second factor was levels of extract concentration. The result showed that the application of aqueous and ethanol extract enhanced all parameters of V. radiata L. germination (percentage of seed germination, rate of seed germination, radicle length, seedling fresh weight). Application of lower concentration (0,25%) of aqueous and ethanol extract increased speed of germination, radicle length, and fresh weight of seed. The application of 75% aqueous extract increased the percentage of germination to 100% than control and another treatment. However, further research is needed to confirm the effect of this plant extract on the vegetative growth of Vigna radiata L.Keyword: Acacia nilotica, aqueous extract, ethanol extract, seed germinatio